2013
DOI: 10.4103/0019-5413.121594
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical comparison of dynamic condylar screw and locking compression plate fixation in unstable distal femoral fractures: An in vitro study

Abstract: Background:Distal femur fractures are difficult to manage and the selection of implant for internal fixation remains controversial. The objective of this study is to establish the relative strength of fixation of a distal femoral locking plate (DFLP) compared with the dynamic condylar screw (DCS) in the distal femur fractures.Materials and Methods:Study was conducted on 16 freshly harvested cadaveric distal femoral specimens, eight implanted with DCS and other eight with DFLP. The construct was made unstable b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
0
10
0
3
Order By: Relevance
“…Para isso, torna-se necessário a realização de ensaios mecânicos específicos, que depende do tipo de material a ser testado, da finalidade a que se destina, do tipo de esforço ao qual será submetido e, também, das propriedades do biomaterial (França et al 2008, Singh et al 2013, Ueno et al 2015. Como o esqueleto apendicular dos animais está sob ação de um conjunto de forças, dentre elas a de compressão, o teste mecânico de compressão axial, atualmente, é o mais utilizado para avaliar a resistência mecânica de biomaterial, principalmente os cilíndricos (Amendola et al 2008, Alves et al 2010, Sonagli et al 2011.…”
Section: Resultsunclassified
“…Para isso, torna-se necessário a realização de ensaios mecânicos específicos, que depende do tipo de material a ser testado, da finalidade a que se destina, do tipo de esforço ao qual será submetido e, também, das propriedades do biomaterial (França et al 2008, Singh et al 2013, Ueno et al 2015. Como o esqueleto apendicular dos animais está sob ação de um conjunto de forças, dentre elas a de compressão, o teste mecânico de compressão axial, atualmente, é o mais utilizado para avaliar a resistência mecânica de biomaterial, principalmente os cilíndricos (Amendola et al 2008, Alves et al 2010, Sonagli et al 2011.…”
Section: Resultsunclassified
“…Locking plates, together with angled blade plates, intramedullary nails and DCS plates, have become one of the most commonly used fixation devices in DFFs [5]. A biomechanical comparison of locking plates and DCS plates shows locking plates to be more stable [6]. Biomechanical studies of digital models have shown that the stability of a DFF fixa tion ły, że sta bil ność ze spo le nia ZKD KU pły ta mi blo kowa ny mi, po zwa la na wdro że nie czyn nych ćwi czeń sta wu ko la no we go w pierw szych dniach po ope ra cji bez ry zy ka za bu rze nia zro stu i de sta bi li za cji ze spo lenia [7].…”
Section: Discussionunclassified
“…Pły ty blo ko wa ne sta ły się obok płyt ką to wych, gwoź dzi śród sz pi ko wych i płyt DCS, jed nym z częściej sto so wa nych ma te ria łów do ze spo le nia ZKD -KU [5]. Bio me cha nicz ne po rów na nie płyt blo ko wanych i płyt DCS wy ka zu je, że pły ty blo ko wa ne są sta bil niej szą kon struk cją [6]. Ba da nia bio me cha niczne prze pro wa dzo ne na mo de lach cy fro wych wy ka za -returning to work.…”
Section: Dys Ku Sjaunclassified
“…Locking plates provides an additional advantage of angular stability of locked screws by which applied load is evenly distributed amongst the component screws and avoids significant load concentration at a single screw bone interface [4,6,7]. This leads to the overall Original Article fixation strength of the locked plate system, equaling the sum of fixation strengths of all screw bone interfaces instead of that of a single component screw as in conventional plating [8].…”
Section: Introductionmentioning
confidence: 99%
“…Voluminous literature [8][9][10] is available showing good to excellent results of locking plates for the treatment of distal femur fracture however none of study has compared the outcome of patients in smoker and nonsmoker. Since smoking affects the bone union time therefore this study was carried out to assess the long term functional outcome of distal femur fracture treated with locking plates and compared the outcome results among smokers and nonsmokers.…”
Section: Introductionmentioning
confidence: 99%